Nano crystalline silver: a breakthrough in treating diabetic foot ulcers - Kaundal, Vishal; Sharma, Vikrant (International Surgery Journal, 2019)
India harbours world’s largest population of diabetic patients thus earning an infamous designation of ‘diabetic capital of the world’. Apart from various metabolic aberrations that are bound to happen in a patient with uncontrolled hyperglycemia, foot ulcers are one of the serious complications that may become limb and life threatening, if not addressed properly. Surgical debridement along with appropriate antibiotics, remain as the mainstay of management of such wounds. Conventional dressing methods involving povidone-iodine and other antiseptic agents have offered limited scope of effective wound healing owing to their inherent toxicity towards fibroblasts. In the present scenario where a large chunk of population crosses over to the list of newly diagnosed diabetics every year, nano crystalline silver has come as a breakthrough in effective management and early healing of diabetic foot ulcers through its effective antimicrobial action and limited toxicity for the host tissue.